Penulisan Esai Akademik dan Strategi untuk Lolos Konferensi Internasional - Febrina Nadelia; Desi Indrawati; Yella Dezas Perdani (Social Economics and Ecology International Journal (SEEIJ), 2020)
Academic writing activities for students are to convey ideas, arguments, and be involved in scientific activities. In academic writing, it is always classified by evidence-based arguments, correct word choice, logic, and structure. Although it is sometimes considered wordy, proper academic writing is one that informs, analyzes, and engages readers directly and critically. Moreover, knowing the stages of academic writing and how to write correctly is also needed in writing essays and motivation letters to pass international conferences selection. Every international conference usually demands conference applicants to prepare their essays and motivation letters comprehensively. Therefore, if students are interested in participating in international conferences, they should try to make interesting essays and motivation letters, both in terms of titles, innovations, and solutions that give new colors in the fields they participate. The purpose of this service through the webinar on academic essay writing and strategies for passing the international conference selection is to provide education and knowledge of writing and scientific thinking skills for students and to motivate and expand their insights to participate actively in international conferences by preparing their essays and motivation letters as the requirements for participating in international conferences. Participants who took part in this webinar were 61 students from Bina Nusantara University Bandung Campus, Pasundan University, UNIBI Bandung, and STIEPAR YAPARI Bandung. There are several series of events held in this webinar. The results of this service showed optimism and positive responses from the participants to make proper and structured writing and encourage their urge to participate actively in international conferences with the initial stages of writing essays and motivation letters.